2020
DOI: 10.7554/elife.52896
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of mRNAs to P granules by condensation with intrinsically-disordered proteins

Abstract: RNA granules are protein/RNA condensates. How specific mRNAs are recruited to cytoplasmic RNA granules is not known. Here, we characterize the transcriptome and assembly of P granules, RNA granules in the C. elegans germ plasm. We find that P granules recruit mRNAs by condensation with the disordered protein MEG-3. MEG-3 traps mRNAs into non-dynamic condensates in vitro and binds to ~500 mRNAs in vivo in a sequence-independent manner that favors embryonic mRNAs with low ribosome coverage. Translational stress … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
204
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(228 citation statements)
references
References 79 publications
24
204
0
Order By: Relevance
“…A recent publication by Lee et al corroborates our findings (Lee et al, 2020). They identified 492 P granule transcripts that precipitate with the intrinsically-disordered P granule factor MEG-3, and they found them to be of low ribosomal occupancy.…”
Section: Discussion Translational Repression Of Mrna Is Necessary Andsupporting
confidence: 91%
“…A recent publication by Lee et al corroborates our findings (Lee et al, 2020). They identified 492 P granule transcripts that precipitate with the intrinsically-disordered P granule factor MEG-3, and they found them to be of low ribosomal occupancy.…”
Section: Discussion Translational Repression Of Mrna Is Necessary Andsupporting
confidence: 91%
“…In contrast, the HRDE-1 loaded 22G-RNAs of P granule dependent piRNA targets (Supplemental Table 1) did not show phasing with ribosomes as observed due to a lack of 3 nucleotide periodicity ( Fig. 4c and d), in agreement with the fact that P granules are devoid of translating mRNAs 36,37 .…”
Section: Translating Mrnas Serve As the Template For 22g-rna Biogenesissupporting
confidence: 79%
“…The non-specific nature of recruitment of mRNAs into RNA granules would suggest that these structures and their associated proteins would bias their regulatory effects more strongly towards longer mRNA molecules, which contain more potential sites for non-specific protein-RNA and RNA-RNA interactions. Indeed, multiple groups have found that stress-induced RNA granules, as well as developmentally induced P granules, are enriched for long mRNA transcripts (Khong et al 2017;Padrón et al 2019;Lee et al 2020). Given the requirement for Fmr1 targets such as Poe/Ubr4 in the maintenance of cell homeostasis, these results are consistent with the model that Fmr1 evolved to maintain uniform translation by counteracting the inherent tendency of long mRNAs to partition into repressive RNPs under stressful conditions.…”
Section: Transcripts From Asd/id Genes Are Enriched In Stress Granulesupporting
confidence: 74%